analisis tingkat daya saing dan faktor-faktor yang mempengaruhi ekspor kayu olahan indonesia ke negara amerika serikat - Armawan, Kadek Krisna; Kusuma Jaya, I Wayan Wita (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 6, Juni 2013 (pp. 277-313), 2013)
Internasional trading is one of the important factors to stimulate the economic growth of a country. International trading can help countries in carrying out any development effort thourgh prioritizing economic sectors that contain of comparative advantage (availability of resources). Indonesia has a great potential in export ow processed wood because of avalibility of abundant resources and geographical location which has a tropical forest. In this study, the problems put forward is how the development of the competitiveness of Indonesian export of processed wood in the period 1992-2011? Whether the export volume variables simultaneously, the rupiah exchange againts the united states dollar and the united states GDP impact export of processed wood Indonesia in 1992-2011 and how the volume exports, the rupiah exchange againts the united states dollar and the united states GDP partially on Indonesian export of wood period 1992-2011? Analytical techniques used in this study are analysis RCA (Revealed Comparative Advantage) and multiple linear regression analysis. The result showed, the average level of competitiveness of Indonesian export of processed timber is 4,4, which means wood export Indonesian has high competitiveness compared with export of processed wood Malaysian and Thailand. Associated with abundant resources Indonesian wood export have factors affecting the export of timber. Amounted to 92,1 percent of export volume variable, the rupiah exchangea gaints the united states dollar and the united states GDP affect the Indonesian export of processed timber from 1992-2011, while the remaining 7,9 percent is influenced by other variables outside of timber exports. Partially, the export volume variable gives a significant and positive effect on the export of Indonesian wood. The rupiah exchange againts the united states dollar gives a significant and negative effect of the export Indonesian wood. Whereas the united States GDP  variable has no effect on the export of Indonesian wood period 1992-2011.
Keywords: Export volume, Kurs exchange, United States GDP